PERILAKU PERAJIN DALAM MENINGKATKAN KINERJA PASAR* - P. Eko Prasetyo (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2007)
This study has taken position for developing of small-scale industry (SSI) is necessary strategy or market conduct policy and market performance. For that objective, the realization steps needed are: (a) re-examining about national development objective; (b) conducting political system restructurization that enable all people has equal right to participate in the economic sectors; (c) allocating and distributing economic resources and production facilities in equitable manner especially for rural people; and also (d) making more deep market penetration for goods and services of SSI through issuing inceptives and positive discrimination policies for SSI in supplying their production input, production process and marketing. Promotion intensification and nourishing cooperation with another kind of enterprise will be a beneficial.